PENGARUH SISTEM INFORMASI AKUNTANSI TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH NAGAN RAYA - Ayu Pratiwi; Sari Maulida Vonna; Mastuti Harmi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2022)
This study aims to determine the influence of the accounting information system (SIA) on the quality of financial reports (KLK) at the Nagan Raya Regency Regent's Office. The approach used is to use quantitative methods through questionnaire data collection. The data analysis technique used simple linear regression statistical analysis. the results of the regression test obtained Y = 20,441, which indicated that the accounting information system was able to substantially influence the financial statement factors. Analysis of the partial test (T) obtained sig (0.022) from alpha (0.005), it can be explained that SIA is able to influence the financial statements of the Nagan Raya Regency Regent's Office. In addition, the results of the coefficient test are known that the effect that occurs is 50.1%. Therefore, the local government, especially the Nagan Raya Regency Regent's Office, must regularly pay attention to and audit the accounting information system that is being run so that the gaps that occur can be identified in order to make improvements as quickly as possible. Agencies not only pay attention to the performance of their employees, but also pay attention to the information system that is being run.Keywords : Quality of Financial Reports, Accounting Information Systems.